1996
DOI: 10.1002/anie.199623631
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic, Enantioselective Addition of Allylsilanes to Aldehydes: Generation of a Novel, Reactive TiIV Complex from TiF4

Abstract: Unique reactivity is shown by the fluorotitanium complex obtained from TiF4 and 1,1′‐bi‐2‐naphthol. It is more reactive than the chloro‐, bromo‐, and alkoxytitanium complexes previously employed and catalyzes the enantioselective additions of allyltrimethylsilane to aldehydes [Eq. (a)], providing an alternative to known methods involving the corresponding organotin reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(59 citation statements)
references
References 32 publications
0
55
0
4
Order By: Relevance
“…75 In addition, Duthaler proposed a ternary transition structure in which the electrophilic titanium center activates the aldehyde and the nucleophilic fluoride bridge to silicon increases the reactivity of allylsilane (Scheme 23). 77 A reaction that proceeds with this transition structure could directly give the silylated adduct with regeneration of the catalyst.…”
Section: Scheme 14mentioning
confidence: 99%
“…75 In addition, Duthaler proposed a ternary transition structure in which the electrophilic titanium center activates the aldehyde and the nucleophilic fluoride bridge to silicon increases the reactivity of allylsilane (Scheme 23). 77 A reaction that proceeds with this transition structure could directly give the silylated adduct with regeneration of the catalyst.…”
Section: Scheme 14mentioning
confidence: 99%
“…

The enantioselective allylation of aldehydes to form homoallylic alcohols is one of the most frequently used carbon-carbon bond-forming reaction in chemical synthesis and, for several decades,h as been at esting ground for new asymmetric methodology.H owever,ageneral and highly enantioselective catalytic addition of the inexpensive,nontoxic, air-a nd moisture-stable allyltrimethylsilane to aldehydes,t he Hosomi-Sakurai [1] reaction, has remained elusive. [2,3] Reported herein is the design and synthesis of ah ighly acidic imidodiphosphorimidate motif (IDPi), whiche nables this transformation, thus converting various aldehydes with aromatic and aliphatic groups at catalyst loadings ranging from 0.05 to 2.0 mol %w ith excellent enantioselectivities.O ur rationally constructed catalysts feature ah ighly tunable active site,a nd selectively process small substrates,t hus promising utility in various other challenging chemical reactions.

…”
mentioning
confidence: 99%
“…[3] To this end, several effective catalytic variants with achiral allylboron reagents, [9,10] allylstannanes, [11][12][13] allyl halides, [14,15] and allyl acetates [16] have been developed. [3,17,18] Despite significant effort, [3] however, ag eneral and broadly applicable allylation of aldehydes with allyltrimethylsilane (3)a sahighly attractive allyl-transfer reagent has proven to be extremely challenging [2,3,19] (Figure 1a). Comparatively,a llylsilanes are considered nontoxic,a ir-a nd moisture-stable,o ften commercially available,a nd easily prepared and handled.…”
mentioning
confidence: 99%
“…Carreira et al reported that allyltrimethylsilane effectively traps HF in the form of fluorotrimethylsilane and propene in the preparation of BINOLate-TiF 2 from 1,1¢-bi-2-naphthol (BINOL) and tetrafluorotitanium. 12 The use of this allyltrimethylsilane HF-trap also worked successfully in the preparation of B-fluoro OXB 2d. Thus, in the presence of allyltrimethylsilane (4 equiv), 11 reacted smoothly with BF 3 ·OEt 2 to afford 2d (Equation 2).…”
Section: Methodsmentioning
confidence: 98%